Completion pancreatectomy or a pancreas-preserving procedure during relaparotomy for pancreatic fistula after pancreatoduodenectomy: a multicentre cohort study and meta-analysis. Issue 11 (5th October 2021) - Groen, J V; Smits, F J; Koole, D; Besselink, M G; Busch, O R; den Dulk, M; van Eijck, C H J; Groot Koerkamp, B; van der Harst, E; de Hingh, I H; Karsten, T M; de Meijer, V E; et al.
Abstract: Background: Despite the fact that primary percutaneous catheter drainage has become standard practice, some patients with pancreatic fistula after pancreatoduodenectomy ultimately undergo a relaparotomy. The aim of this study was to compare completion pancreatectomy with a pancreas-preserving procedure in patients undergoing relaparotomy for pancreatic fistula after pancreatoduodenectomy. Methods: This retrospective cohort study of nine institutions included patients who underwent relaparotomy for pancreatic fistula after pancreatoduodenectomy from 2005–2018. Furthermore, a systematic review and meta-analysis were performed according to the PRISMA guidelines. Results: From 4877 patients undergoing pancreatoduodenectomy, 786 (16 per cent) developed a pancreatic fistula grade B/C and 162 (3 per cent) underwent a relaparotomy for pancreatic fistula. Of these patients, 36 (22 per cent) underwent a completion pancreatectomy and 126 (78 per cent) a pancreas-preserving procedure. Mortality was higher after completion pancreatectomy (20 (56 per cent) versus 40 patients (32 per cent); P  = 0.009), which remained after adjusting for sex, age, BMI, ASA score, previous reintervention, and organ failure in the 24 h before relaparotomy (adjusted odds ratio 2.55, 95 per cent c.i. 1.07 to 6.08). The proportion of additional reinterventions was not different between groups (23 (64 per cent) versus 84 patients (67 per cent); P  = 0.756). The meta-analysis including 33 studies evaluating 745 patients, confirmed the association between completion pancreatectomy and mortality (Mantel–Haenszel random-effects model: odds ratio 1.99, 95 per cent c.i. 1.03 to 3.84). Conclusion: Based on the current data, a pancreas-preserving procedure seems preferable to completion pancreatectomy in patients in whom a relaparotomy is deemed necessary for pancreatic fistula after pancreatoduodenectomy. Abstract : Based on the present cohort study and meta-analysis, a pancreas-preserving procedure seems to be the preferred surgical strategy whenever possible during relaparotomy for pancreatic fistula after pancreatoduodenectomy.